2013
DOI: 10.1007/s00259-013-2456-1
|View full text |Cite
|
Sign up to set email alerts
|

Transient changes in the endocannabinoid system after acute and chronic ethanol exposure and abstinence in the rat: a combined PET and microdialysis study

Abstract: Purpose Recent biochemical and post-mortem evidence suggests involvement of the endocannabinoid system in alcohol drinking behaviour and dependence. Using [ 18 F]MK-9470 small-animal PET imaging, our primary objective was to evaluate in vivo type 1 cannabinoid receptor (CB1R) binding changes in rats subjected to several ethanol conditions: (1) at baseline, (2) after acute intraperitoneal administration of ethanol (4 g/kg) or saline, (3) after 7 days of forced chronic ethanol consumption, and (4) after abstinen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 49 publications
(74 reference statements)
1
36
1
Order By: Relevance
“…In contrast, extracellular AEA levels in the NAc are unaltered by alcohol self-administration and decreased by non-contingent alcohol administration. Alcohol also appears to induce region-specific changes in brain tissue EC levels, with alcohol-induced disruptions consistently observed in striatal regions 30, 45, 46 but not frontal cortical areas 28 consistent with evidence that alcohol consumption is reduced by CB 1 R antagonism in the VTA and NAc, but not PFC 28, 30, 47 .…”
Section: Endocannabinoid Signaling and Rewardsupporting
confidence: 69%
“…In contrast, extracellular AEA levels in the NAc are unaltered by alcohol self-administration and decreased by non-contingent alcohol administration. Alcohol also appears to induce region-specific changes in brain tissue EC levels, with alcohol-induced disruptions consistently observed in striatal regions 30, 45, 46 but not frontal cortical areas 28 consistent with evidence that alcohol consumption is reduced by CB 1 R antagonism in the VTA and NAc, but not PFC 28, 30, 47 .…”
Section: Endocannabinoid Signaling and Rewardsupporting
confidence: 69%
“…As a possible allostatic process, the AEA surges may be resultant from the absence of an AEA release during 1-day acute withdrawal. Indeed, a recent study has found that the AEA release in the rat nucleus accumbens is observed only after acute alcohol, but not chronic alcohol or chronic withdrawal [Ceccarini et al 2013], though other reports showed that acute alcohol decreases [Ferrer et al 2007] or did not change AEA release in this region [Alvarez-Jaimes et al 2009]. AEA and other NAE elevations were detected at 1-day withdrawal, whereas behavioral responses to the FAAH inhibitor URB597 (inhibition of alcohol drinking) were apparent at both 1-day and 1-week withdrawal time points.…”
Section: Discussionmentioning
confidence: 99%
“…With these limitations in mind, a number of observations support the proposed indirect activation of CB1 by ethanol. First, acute ethanol can facilitate eCB levels both in vitro [34] and in vivo [22, 23]. Notably, acute ethanol also inhibits BLA glutamatergic projections to the NAcc and cortico-striatal excitatory transmission via a similarly proposed mechanism [49, 50].…”
Section: 0 Discussionmentioning
confidence: 99%
“…Behavioral cross-tolerance between ethanol and CB1 agonists has been observed for decades [1517] and the eCB system is thought to participate in innate ethanol preference in both rats [18, 19] and mice [20, 21]. Further, both acute and chronic ethanol exposure alter expression levels of the CB1 receptor as well as the endogenous ligands and their respective metabolic and catabolic enzymes [2234]. Similar alterations have been shown in human alcoholics, indicating ethanol-induced changes in this system may be conserved across species [35, 36].…”
Section: 0 Introductionmentioning
confidence: 99%